Elite athlete motor and loading actions on the upper limb in baseball pitching - Gasparutto, X.; van der Graaff, E.; van der Helm, F. C. T.; Veeger, H. E. J. (Procedia Engineering, 2016)
In baseball, pitchers are the players that are most prone to injury. Most injuries occur at the elbow and shoulder of the throwing upper limb. It is widely accepted that understanding the loading in the joints during pitching is a key factor to prevent injuries. To deepen the understanding of the joint actions this study proposes to split the net joint actions into two part: the motor actions and the stability actions representing respectively the actions generating the joint motion and the actions maintaining the joint integrity. The actions represent the actions applied on the distal segment of the joint. Eight youth elite pitchers participated the study and performed 5 fastball pitches while equipped with skin markers. Three pitches per pitchers were used to compute the joint actions with an inverse dynamics method. The results indicate at the elbow a maximal elbow stability moment in adduction (52±5Nm) on the lower arm at maximal external rotation and a motor action in flexion (38±10Nm) during the acceleration phase. At maximal internal rotation the maximal stability shoulder loading occurred, with a pulling force of 520±80N, a downward force of -290±95N and a depression moment of 65±17Nm. The motor actions at the shoulder were mainly a forward force (93±46N) and an exorotation moment (24±12Nm) during the arm acceleration phase. This study suggest that the main action of the shoulder is to stabilise the joint, with a maximal load at maximal internal rotation, and that the main action at the elbow is avoiding hyperextension, with a critical phase at maximal external rotation. Further study is needed to link the stability actions to injury risk.